Extended Bow-Tie model for asset risk and reliability modeling: application to a passenger lift - Vileiniskis, Marius; Remenyte-Prescott, Rasa (2016)
A risk and reliability modelling framework for railway assets based on the Petri Net and the Bow-Tie models is proposed in this paper. A Petri Net model together with the Monte Carlo simulation is used to replicate the projected operational usage of the asset, inspection and maintenance policies and degra-dation of the asset and to estimate the future condition of the asset over time. Statistics obtained from the Petri Net are used as inputs to the Bow-Tie model, which is then used to estimate the risk of a hazardous event. The paper reports on the proposed methodology and the results of a case study of an underground passenger lift. In particular, the likelihood and the consequences of a lift getting stuck in shaft between landings are calculated.